2019
DOI: 10.1007/s13224-019-01268-6
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Postpartum Intrauterine Device in HIV-Infected Women: Experience from a Tertiary Care Center in Côte d'Ivoire

Abstract: Background Immediate postpartum intrauterine device (PPIUD) is a good solution for reducing low contraceptive coverage in developing countries. However, its use in HIV-infected women is poorly documented. The objective of this study was to assess whether the risk of PPIUD complications was higher in HIV-infected women. Methods A retrospective cohort study compared 64 HIV-infected women to 128 HIV-negative women who had had a PPIUD at the University Hospital of Treichville between January 2016 and March 2017, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Within 3 months post-insertion, across 21 studies, the proportion of women with infections ranged from 0% (eight studies) to 7.5% 41. By 6 months follow-up, the proportion of PPIUD-related infections was very similar to earlier follow-up, from 0% in five studies to 5.4% 46. The latter was reported in a retrospective study that included all postpartum genital infections in 128 women in Ivory Coast 46.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Within 3 months post-insertion, across 21 studies, the proportion of women with infections ranged from 0% (eight studies) to 7.5% 41. By 6 months follow-up, the proportion of PPIUD-related infections was very similar to earlier follow-up, from 0% in five studies to 5.4% 46. The latter was reported in a retrospective study that included all postpartum genital infections in 128 women in Ivory Coast 46.…”
Section: Resultsmentioning
confidence: 78%
“…follow-up, from 0% in five studies to 5.4%. 46 The latter was reported in a retrospective study that included all postpartum genital infections in 128 women in Ivory Coast. 46 In the few studies (n=5) in which infection occurrence at 12 months was reported, the proportion of women with infections was ≤3.3%.…”
Section: Reviewmentioning
confidence: 99%